Scanning electron microscopy of the corneal endothelium of ostrich - Pigatto,João Antonio Tadeu (2009)
The aim of this study was to examine the endothelial surface morphology and perform a morphometric analysis of the corneal endothelial cells of ostrich (Struthio camelus) using scanning electron microscopy. Polygonality, mean cell area, cell density and coefficient of variation of mean cell area were analyzed. The normal corneal endothelium consisted of polygonal cells of uniform size and shape with few interdigitations of the cell borders. Microvilli appeared as protusions on the cellular surface. The average cell area was 269±18µm² and the endothelial cell density was 3717±240cells mm-2. The coefficient of variation of the cell area was 0.06, and the percentage of hexagonal cells was 75%. The parameters evaluated did not differ significantly between the right and the left eye from the same ostrich. The results of this study showed that the ostrich corneal endothelial cells appear quite similar to those of the other vertebrates.